MELACAK NALAR HUKUM HAK PENGASUHAN IBU NON MUSLIM; - Iksan Iksan; Ahmad Ali Mashudi (LPPM UNHASY, 2022)
This article is the result of library research. This research is included in the category of normative legal research. This research discussion aims to explain the legal status of non-Muslim mothers in the context of post-divorce child care. The findings of this study are that according to the ulama' of the four schools of thought, the haānah rights of an apostate mother should not be granted. The argument that is built is that haānah does not only take care of physically but also includes children's religious education. The non-Muslim mother is feared to have a direct or indirect influence on the child. The legal status of an apostate also affects legal action. The apostasy reduces the ability to raise children, so the majority of scholars' abort the haānah rights for apostate mothers. KHI explains child custody/haānah in general as regulated in article 105. Parenting rights of non-Muslim mothers are not regulated by KHI. Keywords: Parenting rights, non-Muslim mothers, legal reasoning Daftar Pustaka Abdurrahman. 2015. Kompilasi Hukum Islam di Indonesia. Jakarta: Akademika Pressindo. Al Amin, Habibi.